2014
DOI: 10.1177/1350650114556400
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of lubrication of piston ring of two-stroke marine diesel engine considering the effect of multi-scale grooves on the cylinder liner

Abstract: The method of lubrication for piston ring in some types of low-speed two-stroke marine diesel engines is completely different from those in medium- or high-speed diesel engines since the inner surface of cylinder liners are textured with elliptical grooves in macroscale and honing texture in microscale. In this paper, a numerical model has been developed to study the potential of use of cylinder bore surface texturing, in the form of circumferential oil grooves with different dimensions and densities, to impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…The motion equation of ring should be considered to solve the instantaneous MOFT . In the current study, similar to the previous studies, the motion of ring can be described as md2h0normaldt2=Foil+FaspFbpFt, where F oil represents the force of oil film, F asp represent the force caused by asperity contact, m represents the mass of ring.…”
Section: Mathematical Modelingmentioning
confidence: 69%
See 1 more Smart Citation
“…The motion equation of ring should be considered to solve the instantaneous MOFT . In the current study, similar to the previous studies, the motion of ring can be described as md2h0normaldt2=Foil+FaspFbpFt, where F oil represents the force of oil film, F asp represent the force caused by asperity contact, m represents the mass of ring.…”
Section: Mathematical Modelingmentioning
confidence: 69%
“…The suitable dimple parameters were obtained for the minimum average friction force. Mohamad et al investigated the potential use of circumferential liner grooves to improve the mixed lubrication performance of a ring. It was showed that the optimum grooves can substantially reduce the friction loss of the ring.…”
Section: Introductionmentioning
confidence: 99%
“…The pressure boundary conditions in the axial direction can be expressed as [ 20 ]: where p 1 is the cylinder pressure and p 2 is the gas pressure under the compression ring. In practice, the cylinder pressure varies with time, and the gas pressure under the compression ring is almost equal to ambient pressure.…”
Section: Methodsmentioning
confidence: 99%
“…Zhou et al textured uniform shape dimples with different area densities and depth over diameter ratios on a cylinder liner to obtain higher load-carrying capacity and oil film thickness [ 19 ]. By texturing grooves with suitable shape and size on the cylinder liner, Mohamad et al obtained lower friction and higher hydrodynamic pressure [ 20 , 21 ]. These studies are mainly focused on the flat piston ring-cylinder liner system with dimples/grooves on the liner.…”
Section: Introductionmentioning
confidence: 99%
“…The forces acting on the ring in the axial direction are shown in Fig. 2 and are expressed as follows [18]. The pressure force acting on the ring is given by [19]:…”
Section: Forces Acting On the Compression Ringmentioning
confidence: 99%